Dysregulated Chemokine Signaling in Cystic Fibrosis Lung Disease: A Potential Therapeutic Target - Guan, Xiaoqing; Hou, Yuning; Sun, Fei; Yang, Zhe; Li, Chunying (Current Drug Targets, 2016)
CF lung disease is characterized by a chronic and non-resolving activation of the innate immune system with excessive release of chemokines/cytokines including IL-8 and persistent infiltration of immune cells, mainly neutrophils, into the airways. Chronic infection and impaired immune response eventually lead to pulmonary damage characterized by bronchiectasis, emphysema, and lung fibrosis. As a complete knowledge of the pathways responsible for the exaggerated inflammatory response in CF lung disease is lacking, understanding these pathways could reveal new therapeutic targets, and lead to novel treatments. Therefore, there is a strong rationale for the identification of mechanisms and pathways underlying the exaggerated inflammatory response in CF lung disease. This article reviews the role of inflammation in the pathogenesis of CF lung disease, with a focus on the dysregulated signaling involved in the overexpression of chemokine IL-8 and excessive recruitment of neutrophils in CF airways. The findings suggest that targeting the exaggerated IL-8/IL-8 receptor (mainly CXCR2) signaling pathway in immune cells (especially neutrophils) may represent a potential therapeutic strategy for CF lung disease.
Keywords: lung inflammation